1974
DOI: 10.1002/ar.1091780406
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural observations on the form and distribution of nuage in germ cells of the rat

Abstract: Germ cells of the rat have been studied at the fine structural level from the time they are present in the epithelium of the embryonic gut until near the time of production of mature gametes in the adult. Particular attention has been paid to the form and location of dense, fibrous material (nuage) in the germ cells during that period of the life cycle. The nuage either exists as small discrete bodies in the cytoplasm or as “cementing material” situated in the interstices of mitochondrial clusters. It is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 64 publications
5
94
0
1
Order By: Relevance
“…However, subsequent studies failed to confirm these observations, and it is now widely accepted that mouse oocytes lack such mitochondrial aggregates (1,2). This situation is surprising, because Balbiani bodies have been found in marsupials (29) and many mammalian species including goat (21), rat (30,31), hamster (32), and humans (33)(34)(35), although the function of mammalian Balbiani bodies is unknown.…”
mentioning
confidence: 99%
“…However, subsequent studies failed to confirm these observations, and it is now widely accepted that mouse oocytes lack such mitochondrial aggregates (1,2). This situation is surprising, because Balbiani bodies have been found in marsupials (29) and many mammalian species including goat (21), rat (30,31), hamster (32), and humans (33)(34)(35), although the function of mammalian Balbiani bodies is unknown.…”
mentioning
confidence: 99%
“…Primordial germ cells (PGC) remain sequestered in the extra embryonic mesenchyme at the caudal end of the embryo until the embryonic endoderm is produced and gastrulation is completed, and then with folding of the embryo underway the PGCs begin their migration to yolk sac (16). These undifferentiated germ cells migrate towards and settle in sexually undifferentiated gonad (17,18). According to Kemper and Peters (1987) in rat on postcoital day 10, PGCs are found in the invaginating visceral yolk sac endoderm and the base of allantois.…”
Section: Development Of Ovarymentioning
confidence: 99%
“…In germ cells of both sexes, nuage appeared either as a discrete mass or in association with mitochondrial clusters during the different stages of oogenesis and spermatogenesis. Eddy (1974) suggested that that the CB was a component of the nuage in spermatogenic cells.…”
Section: Nuage Components and Their Contents In Mammalian Spermatogenmentioning
confidence: 99%